The level of satisfaction among orthodontic removable appliances patients - Kamaludin Latifi, Fatin Nadhirah; Evangelina, Ida Ayu; Susilawati, Sri (Padjadjaran Journal of Dentistry, 2012)
Introduction: Patient satisfaction is like many other psychological concepts, it is easy to understand but hard to define. The concept of satisfaction overlaps with similar themes such as happiness, contentment, and quality of life. Satisfaction is not some pre-existing phenomenon waiting to be measured, but a judgment that people form over time as they reflect on their experience. A simple and practical definition of satisfaction would be the degree to which desired goals have been achieved. Methods: The type of this research is descriptive with survey methode. Data is collected through questionnaire with the total sample of 150 respondents. The study population was based on accidental sampling, by which the sample was selected depending on who came to Orthodontic Department of RSGM FKG UNPAD, Bandung by the researcher during the period of the research. Results: The data is then analyzed using Community Satisfaction Index (Indeks Kepuasan Masyarakat) or IKM that which shows that 13 out of 14 indicators are still in B grade and overall IKM value of 7.90%, which means that the level of satisfaction has yet not met the expectation among removable appliances patients in Orthodontic Department of RSGM FKG UNPAD, Bandung. Conclusion: The level of satisfaction among removable appliances patients 0rthodontic are still have not met the patients’ expectation.